(untitled) (Physical Education, Health and Social Sciences, 2025)
This study examines the issues and challenges faced by special education teachers in Gilgit-Baltistan, focusing on the academic, structural, and socio-cultural factors influencing the quality of special education in the region. Drawing on data from 56 teachers across multiple districts, the research evaluates teachers’ perceptions regarding instructional challenges, availability of teaching resources, parental involvement, and cultural attitudes toward disability. A quantitative, descriptive research design was used, employing a structured five-point Likert-scale questionnaire comprising items across four thematic areas: academic barriers, resource availability, home school collaboration, and socio-cultural influences. Descriptive statistics revealed persistent constraints, including limited professional training, inadequate teaching materials (Mean = 2.21), challenges in assessing learners (Mean = 2.39), and insufficient classroom facilities (Mean = 2.86). Parental engagement was reported to be weak, with low levels of participation in educational activities (Mean = 2.41). Cultural beliefs and social stigma also emerged as major barriers, reflected in negative community perceptions toward disability (Mean = 2.32). Independent samples t-test results demonstrated no statistically significant gender differences (p > .05) across all variables, indicating that these challenges are systemic rather than gender-specific. Overall, the findings highlight widespread resource shortages, limited institutional support, and cultural constraints that hinder effective special education, underscoring the need for targeted professional development, improved teaching resources, and culturally informed awareness initiatives to strengthen inclusive practices in Gilgit-Baltistan.